The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Revista Planejamento E Políticas Públicas 2021
DOI: 10.38116/ppp57art3
|View full text |Cite
|
Sign up to set email alerts
|

O Impacto das tecnologias sociais sobre a geração de emprego e renda, e a sustentabilidade ambiental do pequeno agricultor do semiárido cearense

Abstract: A seca é um fenômeno climático predominante no semiárido brasileiro e os pequenos agricultores enfrentam dificuldades na produção devido à escassez hídrica. Nesse sentido, o Programa Uma Terra e Duas Águas (P1+2), que faz parte do Programa de Formação e Mobilização Social para a Convivência com o Semiárido, surge com o intuito de ampliar a oferta de água para a produção agrícola no semiárido, por meio da captação de água da chuva em cisternas. Para verificar se esse programa está correspondendo ao que foi plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…These figures show the low level of schooling of respondents, with most of both groups not having completed basic education. Silva et al (2021) found results very close to these, with 76% of their sample composed of people who did not complete elementary education and 13% without any level of education in formal education. The concentration of interviewees, both beneficiaries and non-beneficiaries, in a low level of schooling may indicate the abandonment of studies for the dedication to work in the field.…”
Section: Socio-economic Profile Of Beneficiaries and Non-beneficiariesmentioning
confidence: 66%
See 4 more Smart Citations
“…These figures show the low level of schooling of respondents, with most of both groups not having completed basic education. Silva et al (2021) found results very close to these, with 76% of their sample composed of people who did not complete elementary education and 13% without any level of education in formal education. The concentration of interviewees, both beneficiaries and non-beneficiaries, in a low level of schooling may indicate the abandonment of studies for the dedication to work in the field.…”
Section: Socio-economic Profile Of Beneficiaries and Non-beneficiariesmentioning
confidence: 66%
“…It is also noted that respondents aged 41 and older constitute a large majority in the two samples analyzed, which totals 80.9% of beneficiaries and 68.5% of non-beneficiaries in the middle-aged and elderly stages. Silva et al (2021), when researching the impact of social technologies on income and environmental sustainability of the small farmer in the semi-arid region of Ceará, found similar results and suggested that it was up to the elderly to administer the agricultural activity, and this The average ages of beneficiaries and non-beneficiaries were 52.9 and 50.5 years respectively. The t-Test of comparison of averages points out that there is no difference between the average ages of beneficiaries and non-beneficiaries, at the level of 5% significance, as well as the Mann-Whitney Test, indicating that there is no difference between the samples and corroborating with the result obtained in the t-Test.…”
Section: Socio-economic Profile Of Beneficiaries and Non-beneficiariesmentioning
confidence: 74%
See 3 more Smart Citations